2011
DOI: 10.1590/s1676-06032011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Composição florística e distribuição altitudinal de epífitas vasculares da Floresta Ombrófila Densa na Serra da Prata, Morretes, Paraná, Brasil

Abstract: Abstract:The floristic survey of vascular epiphytes was done in the northern part of the Prata Mountain Range (48° 41' 59.39" W and 25° 36' 46.39" S), Morretes municipality, comprising 6.3 ha of a slope between 400 and 1,100 m a.s.l., covered by submontane and montane Atlantic Rainforest. The aims of this study were: 1) characterize the vascular epiphytic flora; 2) discuss the species distribution along the slope and in ecological categories; 3) evaluate the floristic similarity among the study area and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
3
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 31 publications
5
20
3
14
Order By: Relevance
“…A similar result was reported by Benavides et al (2006), where hemiepiphytes accounted for 52.4%. However, this result differs from the standard cited by most studies that address epiphytism both in the extra-Brazilian Amazon Nieder et al 2000;Benavides et al 2011) and in different forest types in Brazil (Kersten & Kuniyoshi 2009;Kersten et al 2009b, Neto et al 2009Blum et al 2011), where these authors reported the predominance of characteristic holoepiphytes. In addition to these growth habits, there also occurred accidental and facultative holoepiphytes.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…A similar result was reported by Benavides et al (2006), where hemiepiphytes accounted for 52.4%. However, this result differs from the standard cited by most studies that address epiphytism both in the extra-Brazilian Amazon Nieder et al 2000;Benavides et al 2011) and in different forest types in Brazil (Kersten & Kuniyoshi 2009;Kersten et al 2009b, Neto et al 2009Blum et al 2011), where these authors reported the predominance of characteristic holoepiphytes. In addition to these growth habits, there also occurred accidental and facultative holoepiphytes.…”
Section: Resultscontrasting
confidence: 61%
“…In the subtropical forests of Brazil, Orchidacae is also cited as the most diverse family (Alves et al 2008;Neto et al 2009;Kersten 2010;Blum et al 2011). However, despite not having the highest species richness in the present study, Orchidacae showed the most generic diversity.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…O hemiepifitismo não é uma forma de vida importante no estrato superior das florestas tropicais brasileiras (BLUM et al, 2011;BUZATTO et al, 2008;KERSTEN, 2006;KERSTEN;KUNIYOSHI, 2009;KERSTEN;SILVA, 2001;GIONGO;WACHTER, 2004;) registrado com destaque apenas no trabalhos de Santos (2008) e Petean (2009. Esse predomínio pode estar relacionado à menor oferta hídrica, especialmente a umidade do ar, na encosta estudada, em função da ausência de cursos d'água no local, onde os organismos hemiepífitos estariam ocupando melhor os estratos florestais, por obterem os recursos diretamente do solo, em detrimento das demais epífitas que dependem apenas da precipitação e umidade do ar para sua nutrição, uma vez que as condições ambientais do dossel normalmente são mais xéricas que no solo (BENZING, 1990;LARCHER, 2006).…”
Section: Discussionunclassified
“…Esse predomínio pode estar relacionado à menor oferta hídrica, especialmente a umidade do ar, na encosta estudada, em função da ausência de cursos d'água no local, onde os organismos hemiepífitos estariam ocupando melhor os estratos florestais, por obterem os recursos diretamente do solo, em detrimento das demais epífitas que dependem apenas da precipitação e umidade do ar para sua nutrição, uma vez que as condições ambientais do dossel normalmente são mais xéricas que no solo (BENZING, 1990;LARCHER, 2006). Assim como observado em outros trabalhos com estrutura de epífitas em Florestas Ombrófilas Densas no Brasil (KERSTEN;SILVA, 2005;PETEAN, 2009;BLUM et al, 2011) Orchidaceae e Bromeliaceae sempre obtiveram, juntas, um número elevado de riqueza epifítica.…”
Section: Discussionunclassified